Pathobiology of pulmonary disorders - Pokorski, Mieczyslaw (Springer, 2017)
Pulmonary disorders significantly contribute to the current level of disease burden. Effective disease management is essential for improving clinical outcomes and quality of life. This book highlights the issues involved with diagnosing and managing various pulmonary conditions such as chronic obstructive pulmonary disorders, respiratory tract infections, including those developing as a sequel of antibiotic treatment, and others. Investigations on novel diagnostic procedures and potential biomarkers of diseases are discussed, along with disease presentations and management. Preventive measures related to lifestyle and air quality, with the implications on patients care, are tackled as well. Progress in clinical savvy is inseparably linked with getting an insight into the pathogenesis of a condition. This book presents views and information on the research developments in the rapidly changing field of pneumology. Target readership: clinicians and researchers, family practitioners, and trainees.
Includes index.
Keywords: Lungs -- Diseases.; elektronické knihy; electronic books